Evaluation of Minds in Motion, a fitness program for people living with dementia and their caregivers - Pria Nippak; Jocelyn Badali; Julien Meyer; Housne Begum; Nalini Sen; Mya Rana-Nippak (Aging and Health Research)
Background: Fitness is associated with better physical and mental outcomes in people living with dementia (PWD). This study evaluated Minds in Motion, a program designed to improve the physical fitness of PWD and their care partners (CP). Method: Participants completed an 8-week program combining exercise and mindfulness recreational activities. Data were collected through a retrospective mixed-method design. Participants, staff, and volunteers completed data collection. Results: Participants experienced significant improvements in chair stands (+12.9%), bicep curls (+17.2%), and 8 feet up & go (+10.5%) but not in the chair sit and reach exercise. Almost all of the participants (99%) enjoyed the program and staff and volunteers (99%) self-reported improvement in their skills in working with people with dementia, with a strong reduction in the proportion of staff and volunteers disclosing “very limited skill” in dealing with PWD, from 15 to 18% to 9–12% of respondents. Conclusion: This study, as an extension of the pilot, concluded that Minds in Motion program had a positive impact on PWD and CP's physical functioning following the program fitness training combined with mindfulness recreational activities, which aligned with their reported program satisfaction. The “sit and reach” exercise, may not be appropriate for them. Together, these findings highlight how fitness programs can assist PWD and CP with improved functioning through strength building.